Poznámky k novému občanskému zákoníku - Jílek, Aleš (Gynekolog, 2014)
The article “Notes to the New Civil Code” deals with the substantial changes in the field of the civil law as of the January 2014. First it lists the principals of the Code, next it names some of the legal issues referred to the health care. The new Civil Code covers some of the same material scope as the Law on Health Services therefore it is required for any use to consider the relation between the two laws and its particular provisions and subsequently to decide which is to be applied.
Keywords: péče o pacienta; Patient Care; zákonodárství jako téma; Legislation as Topic; soudní lékařství; Civil Rights; Forensic Medicine; Humans; lidé; občanská práva; Delivery of Health Care; poskytování zdravotní péče